Library and information center management - Stueart, Robert D. (Library Unlimited, 2007)
The latest edition of this management classic sports a fresh new look to complement its updated content. It continues to cover all of the important functions involved in library management and development. New chapters on marketing, team building and ethics have been added; thought provoking mini-cases and other activities introduced or expanded; and more international materials referenced than ever before. A perennial favorite in the classroom, an invaluable reference source for information managers everywhere (editoral review)